Academic Achievement of College Students: The role of the Positive Personality Model - de la Iglesia, Guadalupe (2019)
This research aimed at testing an explicative model of academic achievement of college students. Positive personality traits were hypothesized as the main predictors. Mental health and academic adjustment were tested as mediator variables. This model intended to reflect the main hypothesis that academic achievement is multi-determined and non-intellectual variables play an important role in explaining it. Sample was composed of 256 college students of different majors. The results obtained highlighted the importance of differentiating subjective and objective academic achievement in terms of academic adjustment (AA) and grade point average (GPA), respectively. The explicative model that included positive traits as background variables confirmed the mediating role of mental health and AA in explaining GPA. Sprightliness was the most important predictor of academic achievement in comparison to the other positive traits studied. It is concluded that positive personality traits play an important role in academic outcomes.